Analysis of thermoelastic stress-concentration around oblate cavities in three-dimensional generally anisotropic bodies by the boundary element method. (1st March 2016) - Shiah, Y.C.
Abstract: In this article, stress concentrations around cavities in 3D generally anisotropic bodies are investigated using the boundary element method (BEM), where the associated volume integral is analytically transformed to the boundary. All derivations are based upon the Fourier-series representations of the fundamental solutions, including Green's function of displacements and its derivatives. This approach of analytical transformation has fully restored the BEM's distinctive notion that only the boundary needs to be discretized. The goal of the present work is to investigate the thermoelastic stress-concentration around cavities in 3D anisotropic bodies by use of the analytically transformed boundary integral equation (BIE). The work has fully recovered the BEM's nature of boundary discretization for treating 3D generally anisotropic thermoelasticity. This is the first implemented work that successfully treats thermoelastic problems for 3D generally anisotropic solids by the analytically transformed BIE. In the paper, Interesting phenomena are observed from the analyses of stress concentrations around oblate cavities and some discussions are made.